Models and the Nature of Science: What Mediates Their Implementation in Portuguese Biology and Geology Classes? - Joana Torres; Clara Vasconcelos (MDPI AG, 2021)
Currently, it is considered fundamental to improve students' views of the nature of science (NOS) in science classes. In addition, models are also important in science education, not only as contributors for students to develop their views of the NOS, but also for them to develop conceptual knowledge, as well as inquiry skills. Teachers greatly influence students' learning experience. With the aim to improve prospective science teachers' views of the NOS and about models, and to better understand the factors that mediate the translation of their views into their classroom practices, a research project was conducted. An intervention programme was applied, and prospective science teachers' classes were observed. Data were collected, encompassing a diverse set of data sources: (i) questionnaires and interviews (given to prospective science teachers before and after the intervention programme); (ii) prospective science teachers' lesson plans and portfolios: (iii) videotapes and observations of the classroom instruction; (iv) and, lastly, final interviews were given to both prospective science teachers and their school supervisors. Although prospective science teachers have improved their views regarding the NOS and models, they taught about the NOS and used models in very different ways. Some factors that mediate the translation of teachers' views and some educational implications will be discussed.